Implementation of Science Learning Oriented to Socio-Scientific Issues on Ecology and Biodiversity Material in Indonesia to Improve Learning Outcomes and Environmental Awareness Attitudes - Elcye Apema; Fitra Suzanti; Azhar Azhar (Postgraduate, University of Mataram, 2025)
Science education at the junior high school level plays a crucial role in developing scientific thinking skills, scientific literacy, and environmental awareness. However, conventional teaching practices often result in low student understanding and limited environmental consciousness. This study aimed to examine the effect of Socio-Scientific Issues (SSI)-based science learning on the cognitive learning outcomes and environmental awareness of seventh-grade students at SMPN 7 Pangkalan Kuras, as well as the relationship between these variables. The study sample consisted of 43 students, divided into an experimental class (21 students) receiving SSI-based learning and a control class (22 students) receiving conventional instruction. Data were collected through written tests (multiple-choice questions) and environmental awareness questionnaires, then analyzed. The results showed that the average cognitive learning outcomes of the experimental class (75.45) were higher than those of the control class (63.81) and students’ environmental awareness in the experimental class (75.27) was also higher than in the control class (70.12), indicating that SSI effectively enhances both conceptual understanding and environmental concern. These findings provide valuable reference for teachers in implementing contextual and meaningful learning approaches that foster students’ social and ecological responsibility